Epstein-Barr virus latent membrane protein 1 subverts IMPDH pathways to drive B-cell oncometabolism. - Eric M Burton; Davide Maestri; Shaowen White; Jin-Hua Liang; Bidisha Mitra; John M Asara; Benjamin E Gewurz (PLoS Pathogens)
Epstein-Barr virus (EBV) is associated with multiple types of cancers, many of which express the viral oncoprotein Latent Membrane Protein 1 (LMP1). LMP1 contributes to both epithelial and B-cell transformation. Although metabolism reprogramming is a cancer hallmark, much remains to be learned about how LMP1 alters lymphocyte oncometabolism. To gain insights into key B-cell metabolic pathways subverted by LMP1, we performed systematic metabolomic analyses on B cells with conditional LMP1 expression. This approach highlighted that LMP highly induces de novo purine biosynthesis, with xanthosine-5-P (XMP) as one of the most highly LMP1-upregulated metabolites. Consequently, IMPDH inhibition by mycophenolic acid (MPA) triggered death of LMP1-expressing EBV-transformed lymphoblastoid cell lines (LCL), a key model for EBV-driven immunoblastic lymphomas. Whereas MPA instead caused growth arrest of Burkitt lymphoma cells with the EBV latency I program, conditional LMP1 expression triggered their death, and this phenotype was rescuable by guanosine triphosphate (GTP) supplementation, implicating LMP1 as a key driver of B-cell GTP biosynthesis. Although both IMPDH isozymes are expressed in LCLs, only IMPDH2 was critical for LCL survival, whereas both contributed to proliferation of Burkitt cells with the EBV latency I program. Both LMP1 C-terminal cytoplasmic tail domains critical for primary human B-cell transformation were important for XMP production, and each contributed to LMP1-driven Burkitt cell sensitivity to MPA. Metabolomic analyses further highlighted roles of NF-kB, mitogen activated kinase, and protein kinase C downstream of LMP1 in support of XMP abundance. Of these, only protein kinase C activity was important for supporting GTP levels in LMP1 expressing Burkitt cells. MPA also de-repressed EBV lytic antigens, including LMP1 itself in latency I Burkitt cells, highlighting crosstalk between the purine biosynthesis pathway and the EBV epigenome. These results suggest novel oncometabolism-based therapeutic approaches to LMP1-driven lymphomas.